Red Palm Oil from Crude Palm Oil Refinement Using The Acid Degumming Method - Saputra, Hendra; Rantawi, Azhar Basyri; Siregar, Ahdiat Leksi; Rahardja, Istianto Budhi; Simatupang, Dimas Frananta (International Journal of Applied Research and Sustainable Sciences, 2024)
Red Palm Oil (RPO) is the result of refining Crude Palm Oil (CPO). In further processing to obtain cooking oil, several processes are undergone to produce a clear oil, which is very different from its original product, CPO. RPO is rich in beta-carotene and its refining process does not include bleaching. The production of RPO utilizes the acid degumming method with different acid variations, namely phosphoric and sulfuric acid, with varying concentrations of 0.05% and 0.075%. The results showed that the average percentage of RPO produced reaches 44.05%. Furthermore, the quality analysis of RPO also meets the SNI-3741-1995 standards (quality standard of cooking oil), with the average of free fatty acid value of 1.41% (max 3%), peroxide value of 1.04 mg oxygen/100 g (max 1.6 mg oxygen/100 g), and moisture value of 0.04% (max 0.3%).